Complete verification of strong BSD for many modular abelian surfaces over ${Q}$ - Timo Keller; Michael Stoll (Forum of Mathematics, Sigma)
We develop the theory and algorithms necessary to be able to verify the strong Birch–Swinnerton-Dyer Conjecture for absolutely simple modular abelian varieties over